A New Fuzzy Sliding Mode Controller for 2-DOF Aero System with Pitch Disturbance - Kumawat, Gaurav; Goswami, Niraj Kumar; Vajpai, Jayashri (Applied Science and Engineering Progress, 2025)
The two-degree-of-freedom aero flight control simulator is a nonlinear, unstable, and multi-input multi-output system with gravitational disturbance in its pitch dynamics. Its attitude control is a challenging task with linear controllers. The fuzzy controller by parallel distributed compensation uses a combination of linear controllers. It is a simple method, but exhibits poor tracking performance under disturbance. This study presents a design of a fixed structure fuzzy sliding mode controller to track the desired trajectory for this system. A sliding mode controller is combined with the fuzzy controller using an integral sliding surface to overcome gravitational disturbance and track the attitude. Lyapunov’s method verifies the stability of the closed-loop system. To validate the proposed design, numerical simulations are carried out and compared with existing methods. The tracking responses of yaw and pitch point out fast convergence of error with minimum settling time in the presence of matched disturbances.